Pengaruh Kompetensi SintaksisTerhadap Keterampilan Menulis Eksposisi Mahasiswa Prodi Pendidikan Bahasa Indonesia UNM - Usman Usman; Johar Amir (Seminar Nasional LP2M UNM, 2019)
The study aims to: 1) describe the level of syntactic competence of Bahasa Indonesia Department of Universitas Negeri Makassar students; (2) describe the exposition writing skills of Bahasa Indonesia Department of Universitas Negeri Makassar students; and (3) prove the significant effect of syntactic competence toward the skills of writing exposition of Bahasa Indonesia Department of Universitas Negeri Makassar students. This research is quantitative research in the form of ex post facto. The population of the data is the whole students of fourth semester in Bahasa Indonesia Department of Universitas Negeri Makassar. The samples were taken by simple random sampling and assigned Class B with 43 students. The data collection technique is a test. The collected data were analyzed by using analysis of descriptive statistics and statistical simple linear regression test. The results of the study show that : (1) the level of syntactic competence of Bahasa Indonesia Department of Universitas Negeri Makassar students is relatively adequate while the average obtained in the test of competence syntax is 70, the highest score is 88, and the lowest is 40; (2) the exposition writing skills of Bahasa Indonesia Department of Universitas Negeri Makassar students are relatively adequate with the average, the highest, and the lowest score are consecutively 74.6, 90, and 50 ; and (3) The effect of syntactic competence toward the exposition writing skills of Bahasa Indonesia Department student of Universitas Negeri Makassar is exist. Thus, it be concluded that the syntactic competence affect the skills of writing exposition of Bahasa Indonesia Department of Universitas Negeri Makassar students. Based on the results, we suggested that the students are given the knowledge of more in-depth syntactic devices before giving the writing task and the students are provided the knowledge and training related to the aspects of the effective sentences, active-passive voice, assignment words and the use of spelling for Bahasa Indonesia (writing letters and using the prefix di- and preposition di)